Teknologi Tepat Guna (TTG) Berupa QR Code Sebagai Media Informasi Desa Sambirejo Kabupaten Jombang - Vanni Alivyah Krisnandela; Diva Aisyah Maryam; Dhian Satria Yudha Kartika (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
This research is entitled "Appropriate Technology in the form of QR Qode as Information Media for Sambirejo Village, Jombang Regency". With the aim that this technology can be used as a media guide for information quickly and get a response or response quickly as well. Based on the problems found in the field, there are still many outsiders who do not know the potential in Sambirejo Village. Therefore, the role of technology is needed in information media related to Sambirejo Village through the creation of a QR code in the form of pamphlets and brochures. The method used in this study is a qualitative research method with an analysis of excess pressure on a condition through ways of thinking, data collection techniques through observation and storage. From the results of the study it can be concluded that the use of QR Qode technology can be adapted to its function with the environmental, ethical, cultural, social, political and economic aspects of the community concerned.